EVIDENCE OF LONG TERM BENEFIT OF MORBIDITY REDUCTION DUE TO PRAZIQUANTEL TREATMENT AGAINST SCHISTOSOMA MANSONI IN KIGUNGU FISHING VILLAGE IN ENTEBBE, UGANDA - Odongo-Aginya, Emmanuel Igwaro; Kironde, F K; Lyazi, M I; Sempewo, H; Oliveira, Rodrigo Correa (African Journal of Infectious Diseases (AJID), 2011)
Praziquantel (PZQ) is efficacious against Schistosoma mansoni. This was prospective cohort study. This study was carried out at Kigungu fishing village, Entebbe, Uganda. The goal of the study was to establish cost effective regiment for mass drug administration (MDA) of Praziquentel in the morbidity reduction of S.mansoni infection. In January 2004, nine hundred and forty five (945) participants were registered in this study. Our analysis was based on examining microscopically three slides prepared from each of 945 stool specimens delivered by each of the participant using modified Kato/Katz method. These included male and female, children and adults living in Kigungu fishing village in Entebbe Uganda. In total 901, cohorts were re-examined for infections clearance six months later in July 2004 and 18 months later in June 2005, 625 cohorts were again re-evaluated for S.mansoni infections after the baseline study. At baseline, (448) of 945 (47.5%) cohorts were S. mansoni positive. All these participants were treatment with a single oral dose of praziquantel at 40mg/kg. At the same time, 495 (52.5%) were S. mansoni negative. Of the 625 (66.3%) cohorts who came back for final review, 80 (12.8%) were still positive for S. mansoni while 210 (33.6%) remained negative after the base line treatment with praziquantel. On the other hand 103 (16.3%) of cohorts who were initially negative at the base line became S.mansoni positive after 18 months and 213(34.1%) remained negative for S.mansoni. The force of re-infection after six months was significant {(P=0.0001), (OR 0.47) CI at 95% (0.31-0.71)}. Nevertheless the force of reinfection was not significant after 18 months {(P=0.766), (OR 0.95) CI at 95% (0.68-1.34)}.The geometric mean eggs excretion of the 80 cohorts who were S.mansoni positive at 18 months was 151.967.This did not reach the geometric mean egg excreted by the same cohorts at baseline which was 285.05. The egg excretion was reduced by 46.8%. Similarly there was marked decrease in clinical symptoms amongst the cohorts. Our study suggests evidence of long-term benefit of praziquantel in Kigungu and that a yearly administration of praziquantel to the community could be a regiment for mass drug administration (MAD) for this community to control schistosomiasis morbidity.